الفروق بين الدافعية العقلية والنهوض الأكاديمي تبعا لمتغير النوع الاجتماعي "الذكور والإناث" لدى طلاب كلية التربية بالوادي الجديد - باشا، نجاة عدلي توفيق; واعر، نجوى أحمد عبدالله; منسي، محمود عبدالحليم حامد; زاهر، هند جلال محمد Zaher, Hend Jalal Mohammed (جامعة أسيوط - كلية التربية, 2022)
هدف البحث الحالي إلى الكشف عن الفروق بين الدافعية العقلية والنهوض الأكاديمي تبعا لمتغير النوع الاجتماعي (الذكور والإناث) لدى طلاب كلية التربية بالوادي الجديد، وتكونت عينة البحث من (١٩٦) طالبا وطالبة بمتوسط عمر قدره (20.6) سنة وانحراف معياري قدره (٠,٧٦٥) من طلاب الفرقة الثالثة بكلية التربية بالوادي الجديد للعام الجامعي 2021/2022م، وتمثلت الأدوات في مقياس الدافعية العقلية إعداد الباحثة، ومقياس النهوض الأكاديمي إعداد أمل عبد المحسن (٢٠١٨)، وتوصلت نتائج البحث أنه لا توجد فروق ذات دلالة إحصائيا بين متوسطي درجات الذكور والإناث في جميع الأبعاد الفرعية والدرجة الكلية لمقياس الدافعية العقلية، كذلك لا توجد فروق ذات دلالة إحصائيا بين متوسطي درجات الذكور والإناث في جميع الأبعاد الفرعية والدرجة الكلية لمقياس النهوض الأكاديمي. This research aimed at discovering the differences between mental motivation and academic buoyancy according to gender variable (Male and female) for the students of New Valley Faculty of Education. The research sample included (196) students, with average age (20.6) and standard deviation (0.765) from the third year students of New Valley, Faculty of Education for the academic year 2021/2022. The research tools are a scale for mental motivation was prepared by the researcher and a scale for academic buoyancy was prepared by Amal abd El-Mohsen (2018).The results of the research revealed that, there is no statistically significant differences between the average score of male and female in all sub- dimensions and total score of the mental motivation scale and there is also no statistically significant differences between the average score of male and female in all sub- dimensions and total score of the academic buoyancy scale.
Keywords: علم النفس التربوي -- التعليم الجامعي -- النوع الاجتماعي -- طلبة الجامعات